Influence of daytime napping on hormonal and psychometric variables of professional male basketball players during increased game frequency period crossing Ramadan intermittent fasting: a crossover research design with repeated assessments - Seifeddine Brini; Urs Granacher; Julio Calleja Gonzalez; Georgian Badicu; Fatma H. Yagin; Filipe Manuel Clemente; Javier Raya Gonzàlez; Jennifer A. Kurtz; Safaa M. Elkholi; Madawi H. Alotaibi; Hadi Nobari; Luca Paolo Ardigò (Journal of Men's Health, 2024)
A diurnal nap during Ramadan intermittent fasting (RIF) could significantly reduce fatigue. This study aimed to assess the effects of a 45-min daytime nap on hormonal and psychometric variables during an increased basketball game frequency period that crosses RIF. 28 participants from two professional basketball clubs were selected. Participants were divided into two groups: a 45-min nap group (NAP, n = 14) and an active control group (CON, n = 14). Both groups experienced an increased game frequency when crossing the RIF. During week 1 and 4 of RIF, players were assessed for testosterone to cortisol ratio, body composition (body mass, body mass index and body fat percentage), sleep quality index survey results, well-being indices (sleep, fatigue, stress and delayed onset of muscle soreness (DOMS)), weekly internal training load (session rating of perceived exertion (RPE)), heart rate frequency, dietary intake and recovery state (Total Quality Recovery (TQR)). In this study, a group-by-time interaction (p = 0.02, effect size (ES) = 0.35, small) was observed for RPE, although NAP showed a lower value. Significant group-by-time interactions for TQR and DOMS (p = 0.02, ES = 0.38, small; p = 0.04, ES = 0.30, small; p = 0.045, ES = 0.28, small), with a better value of NAP. A 45-min nap during an increased game frequency period crossing RIF may improve professional basketball performance by providing a better way for recovery.